تكنولوجيا الذكاء الاصطناعي ودورها في ظهور المؤسسات الناشئة، لمحة عن التجربة الألمانية - بوخاتم، لخضر (My University, 2024)
هدفت هذه الدراسة لتعرف على مفهوم تكنولوجيا الذكاء الاصطناعي كواحدة من أهم أنواع التكنولوجيا والتقنيات التي أصبحت تتزايد قيمتها وتأثيرها على مختلف جوانب الحياة، وتم تخصيص هذه الدراسة لمعرفة الدور الذي يلعبه الذكاء الاصطناعي في تأثير على نموذج أعمال المؤسسات الناشئة، حيث تم اختيار النموذج الألماني لمعرفة واقع العلاقة بين الذكاء الاصطناعي والمؤسسات الناشئة. وعبر استعراض مجموعة من الأطر والبيانات والعوامل تبين أن دولة ألمانيا وبفضل ما تمتلكه من قدرات تكنولوجية، بشرية، مالية، ثقافية وغيرها من العوامل الأخرى استطاعت أن تكون من أوائل الدول على الصعيد العالمي التي نجحت في توفير بيئة مناسبة التي ساعدت على احتضان الذكاء الاصطناعي واستغلاله في توفير فرص لزيادة معدلات الابتكار وإنشاء المؤسسات الناشئة التي تقوم على الذكاء الاصطناعي. الكلمات المفتاحية: الذكاء الاصطناعي، المؤسسات الناشئة، ألمانيا. Abstract This study aimed to explore the concept of Artificial Intelligence (AI) technology, which has emerged as one of the most significant advancements in the field of technology. AI has rapidly gained value and is exerting a profound impact on various aspects of our lives. This study focuses on examining the impact of artificial intelligence on the business models of startups, the German model was selected to gain insights into the relationship between artificial intelligence and startups. Through reviewing a set of frameworks, data, and factors, it becomes evident that Germany, thanks to its technological, human, financial, cultural, and other capabilities, has been able to be one of the leading countries globally that succeeded in providing a suitable environment that helped embrace and leverage artificial intelligence (AI) in order to increase innovation rates and establish AI-based startups. .Keywords: Artificial Intelligence, Startups, Germany
Artificial Intelligence Technology and its Role in the Emergence of Startups, an Overview of the German Experience